MARKET ORIENTATION AND ENTREPRENEURIAL EFFECT OF WINEMAKERS (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2019)
The method of interviews was used to conduct a case study whose objective was to determine the market orientation and entrepreneurial effect of four winemakers in Osijek-Baranja and Vukovar-Srijem Counties. The study showed that the four interviewed winemakers did not have a marketing orientation in the sense of the marketing budget and capacity or in the sense of market orientation. Even though the winemakers are aware of the importance of using marketing in the modern world, their inadequate knowledge of marketing and the absence of a marketing department make them mostly sales-oriented. If the winemakers wish to be competitive in the Croatian and international markets and compete against European winemakers, they must increase their market orientation and turn their sales orientation into marketing.